The rediscovery of Epigomphus sulcatistyla Donnelly, 1989, with a description of its larva and female (Odonata: Gomphidae) - Novelo-Gutiérrez, Rodolfo; Gómez-Anaya, José Antonio (Zootaxa, 2024)
The larva of Epigomphus sulcatistyla Donnelly, 1989 is described, figured and compared with other described Mexican larvae. It is characterized by 3rd antennomere spindle-shaped, almost twice longer than its widest part; ligula with a ventral row of eight short, truncate teeth on middle; abdomen lateral spines on S7–9 slightly divergent; male epiproct dorsal tubercles rounded apically and divergent distally. It differs from other Mexican species mainly in shape of 3rd antennomere, number of teeth on ligula, serrations on lateral margins of S8–9, and shape of cerci. Also, the hitherto unknown female is described, for the first time, based on four teneral female from reared larvae.